Moving for Love: Interracial Marriage and Migration in Brazil - Chinyere Osuji (Social Sciences, 2024)
The link between marriage and migration is usually considered in terms of international migration. However, domestic migration provides another lens in which to view this connection. In Brazil, despite the large migration from the northeast to the southern regions in the twentieth century, the role of domestic migration in race-mixing has been unacknowledged. Since race in Brazil is highly regionalized, with black and brown Brazilians comprising most northern regions and white Brazilians being in the majority of the southern areas of the country, migration can open possibilities for interracial marriage that are less likely to occur for non-migrants. At the same time, as gender plays an important role in opportunities for intermarriage, the effects of migration likely vary according to intersections of race and gender. An examination of the data on marital unions from the 2009 Brazilian National Household Survey, which includes large numbers of earlier cohorts of mass migration, demonstrates the influence of migration on interracial marriage. This study finds that the effect of migration on the odds of being interracially married (in comparison with being in a same-race marital union) vary according to the race and gender of the spouse. This study is one of the first to tie together two demographic phenomena—migration and interracial marriage—that have not previously been examined in the Brazilian context. It also provides a new lens through which to understand interracial marriage in Brazil and has implications for future studies of family formation in Latin America and the Caribbean.